Answer:
B. 3x^2 - 2x - 1.
Step-by-step explanation:
(f + g)x = f(x) + g(x)
= -4x + 3 + 3x^2 + 2x - 4
Adding like terms we get the answer:
= 3x^2 - 2x - 1.
Nine I believe, because fifth teen divided by five equals three
three times three equals nine.
Answer:
15:37 or 3:37
Step-by-step explanation:
3/4=0.75
0.75+9.22=9.97
5+9.97=14.97
Answer:
Hope it helps!
Step-by-step explanation:
Sub y=5x into y=2x+3
so
5x=2x+3
3x=3
x=1
plug x=1 into y=5x
y=5
Checking work
Plug (1,5) into y=2x+3
5=2(1)+3
5=5
Plug (1,5) into y=5x
5=5(1)
5=5